Adversity Qoutient pada Mahasiswa Penghafal Al-Qur'an selama Program Belajar Jarak Jauh (PBJJ) di Asrama Tahfidz Aisyah Al-Amin Banjarmasin - Ni'mah, Raidhatun; Fadhila, Mahdia; Musfichin, Musfichin (Sultan Idris Journal of Psychology and Education, 2022)
One of the efforts to prevent the spread of Corona virus among academics is to implement a distance learning program. This policy also applies to students who live in Tahfidz dormitories, so that students not only study from home but also memorize the Qur'an at home. This study aims to reveal the problems of memorizing the Qur'an and knowing the adversity qoutient of students through recounting experiences during college and memorizing the Qur'an from home. The method used in this research is qualitative with a narrative approach. The subject is a student who has studied and memorized the Qur'an from home. Data collection techniques through in-depth interviews. Analysis of the data used is a narrative analysis technique by Creswell. Data validity using source triangulation technique. The results of the study found that the adversity quotient of the three students who memorized the Qur'an was different. The difference in adversity qoutient in the three subjects can be seen in the ability to control oneself, the point of view of guilt, recognition and ways of being responsible for negligence, limiting the range of difficulties, and perceptions of difficulties and their causes.